An evaluation of the effectiveness of government–non-profit organisations partnership in the delivery of social services. Issue 5 (4th July 2022) - Nwauche, Sokeibelemaye
ABSTRACT: This paper evaluates the effectiveness of the partnership between the government and the non-profit organisations (NPOs) that they fund to deliver social services. The paper evaluates the effectiveness of government–NPOs partnership through the prism of the existing monitoring process. The findings suggest that the monitoring process tends to focus more on the institutional processes that govern the operations of NPOs and less on generating information on the performance and impact of NPOs in the long term. The emphasis on institutional processes undermines our understanding of the effectiveness of the partnership and calls for a systematic process that focuses on outcome-oriented monitoring mechanisms.